Evaluation of the joint effect of the incorporation of mechanically deboned meat and grape extract on the formulation of chicken nuggets. (June 2017) - Tournour, Hernán H; Cunha, Luís M; Magalhães, Luís M; Lima, Rui C; Segundo, Marcela A
The proximate composition, instrumental and perceived appearance of chicken nuggets formulated with varying contents of mechanically deboned chicken meat and varying concentrations of grape pomace extract were evaluated, with the choice of formulations following a central composite design. Significant differences (P < 0.05) in fat content were mainly associated to the extent of mechanically deboned chicken meat incorporation. Colour variables ( CIE a* and b *, and Whiteness index) varied significantly (P < 0.05), with redness (a*) being the variable most influenced by the incorporation of mechanically deboned chicken meat. Whiteness index decreased with added mechanically deboned chicken meat and grape pomace extract. Response surface was applied to identify formulations with higher acceptance scores. Correspondence analysis of open-ended comments complemented the information obtained from overall acceptance, adding valuable descriptive attributes of nugget samples. Thus, addition of grape pomace extract up to 120 mg/kg and mechanically deboned chicken meat up to 15 g/100 g did not adversely affect the perceived appearance of chicken nuggets. Mechanically deboned chicken meat and grape pomace extract can be successfully used for the elaboration of novel products, for different market segments, with healthy connotations highlighted by antioxidant properties retained by the grape pomace extract.